New sex-determination system in the genus Panstrongylus (Hemiptera: Reduviidae) revealed by chromosomal analysis of Panstrongylus lutzi - Santos, Silvia Menezes dos; Pompolo, Silvia das Graças; Gonçalves, Teresa Cristina Monte; Freitas, Simone Patricia Carneiro de; Rangel, Elizabeth Ferreira; Santos-Mallet, Jacenir Reis dos (Biomed Central Public Health, 2016)
Panstrongylus lutzi (Neiva & Pinto, 1923) is a triatomine species native to Caatinga habitats in north-eastern Brazil. It is considered an important vector of Chagas disease in this region, presenting high rates of natural infection with Trypanosoma cruzi Chagas, 1909, and readily invading houses by flight. This study describes a previously unknown chromosomal sex system in the genus Panstrongylus based on P. lutzi. Fifth-instar and male adults of P. lutzi originating from municipality of Várzea Alegre, Ceará (Brazil) were analysed. Chromosomal analyses of male meiotic process were done by Giemsa staining. Chromosomal analyses of male meiosis reveal a diploid chromosome number of 24 chromosomes (20 autosomes plus X1X2X3Y). During meiotic prophase I, the sex chromosomes remained close together, forming four heteropycnotic chromocenters in zygotene, and a single chromocenter in pachytene and diplotene. Still at the diplotene stage, each one of the ten autosomal bivalents showed an evident chiasma. In metaphase I, the four sex chromosomes appeared clearly separated. The three X chromosomes were the smallest of the complement and isopycnotic with respect to the Y chromosome. Two bivalents appear larger, whereas the other eight showed no significant difference in size. Karyotype analysis of P. lutzi revealed a new sex system in the genus Panstrongylus. This result is of utmost importance to karyosystematics of P. lutzi, and demonstrates the need for further studies of this type in the subfamily Triatominae.
Keywords: Cytogenetics; Karyosystematics; Triatominae